2020
DOI: 10.1016/j.toxrep.2019.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Lipoteichoic acid reduces antioxidant enzymes in H9c2 cells

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
7
1
Order By: Relevance
“…When cells are stimulated with pathological stress, Nrf2 is released from Keap1, transferred to nucleus to bind the anti-oxidant response element, and promote the transcription and expression of HO1 and NQO1 [ 39 , 40 ]. Recently study showed that the highest lipoteichoic acid induced oxidative stress injury, which was associated with the increased mRNA levels of Nrf2 in H9c2 cells [ 41 ]. Li et al further found that activation of Nrf2 signaling pathway alleviated myocardial I/R injury by reducing myocardial oxidative stress [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…When cells are stimulated with pathological stress, Nrf2 is released from Keap1, transferred to nucleus to bind the anti-oxidant response element, and promote the transcription and expression of HO1 and NQO1 [ 39 , 40 ]. Recently study showed that the highest lipoteichoic acid induced oxidative stress injury, which was associated with the increased mRNA levels of Nrf2 in H9c2 cells [ 41 ]. Li et al further found that activation of Nrf2 signaling pathway alleviated myocardial I/R injury by reducing myocardial oxidative stress [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…H9c2 cells were subjected to H 2 O 2 and Hypoxia (Hyp) treatment. Figure 3 a, b show upregulation of ROS and hypoxia injury-related markers Catalase 23 – 25 and Hif-1α 26 respectively validated by real-time qPCR, showing upregulation after injury for both the markers. Also, Adamts4 and Collagen-III 27 , 28 expression at mRNA levels shows elevation after both stress treatments (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…All the in-vitro experiments were performed on H9c2, rat ventricular cardiomyoblast cell line. The cells were cultured in Dulbecco’s modified Eagle’s medium (AT007, Himedia) supplemented with 10% FBS (RM10409, Himedia) and 1% penicillin/streptomycin (Pen-Strep) cocktail (15140122, Invitrogen) maintained at a sterile humidified CO 2 incubator at 5% levels and 37 °C 23 . The cells were used for further experiments at about 75–80% confluency.…”
Section: Methodsmentioning
confidence: 99%
“…ROS production was quantified using two fluorescent dyes, H 2 DCFDA and DHE, as previously reported ( Fernández-Rojas et al 2020 ). Cells were seeded (28,000 to 37,500 cells/cm 2 ) in 96-well fluorescence plates and allowed to adhere for 24 h. Subsequently, the cells were treated with GlcN for 6 h with or without the pre-treatment with 10 μM OSMI-1 for 24 h or treated with 1 mM H 2 O 2 for 2 h, as a positive control.…”
Section: Methodsmentioning
confidence: 99%